La jurisprudence française en matière de santé publique, XIXe et XXe siècles - Christophe Bouvier (Criminocorpus)
Upon reading the decisions of the Court of Cassation, regional or national epidemic crises emerge. It is possible to see over the course of these two centuries of practice the establishment of organizational practices and methods whose purpose is to prevent the appearance or spread of the disease. Citizens will resort to the supreme jurisdiction to find someone responsible for the health crisis or prevent a constraint perceived as unfair. The article will approach the epidemic episodes of the 19th and 20th centuries through the prism of public health case law.